(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The use of technology in History teaching is not a new phenomenon, but its impact has been varied depending on the context, teachers and, more importantly, the nature of the innovation. For years, I have come across the “history is boring” comment ad nauseum. For some History teachers, the adoption of technology in the classroom might seem to be the antidote to this problem. One of the most common pieces of Information and Communications Technology (ICT) to be used in the classroom is Microsoft’s Power Point program. A common, but not necessarily proven assumption is that if the History teacher employs this program then the classroom will be set alive with learner participation and enjoyment. The contention in this essay is that the technology in the History classroom is what the teacher makes it – implying that on its own Power Point can not create an active teaching and learning process. To be more specific, from a constructivist point of view, History teaching and learning is an interactive process whereby the learners are expected to “do History,” that is, to practice the construction of their own histories with the guidance of the teacher and it is up to the teacher to create a particular learning atmosphere and culture in his/her history classroom.